The Black Flamingo - Atta, Dean (Balzar + Bray, an imprint of HarpercollinsPublishers, 2020)
"Michael is a mixed-race gay teen growing up in London. All his life, he's navigated what it means to be Greek-Cypriot and Jamaican--but never quite feeling Greek or Black enough. As he gets older, Michael's coming out is only the start of learning who he is and where he fits in. When he discovers the Drag Society, he finally finds where he belongs--and the Black Flamingo is born. Told with raw honesty, insight, and lyricism, this debut explores the layers of identity that make us who we are--and allow us to shine"--FantasticFiction.com.